2019
DOI: 10.3390/molecules24203681
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship between the S1 Domain and Its Molecular Functions Derived from Studies of the Tertiary Structure

Abstract: S1 domain, a structural variant of one of the “oldest” OB-folds (oligonucleotide/oligosaccharide-binding fold), is widespread in various proteins in three domains of life: Bacteria, Eukaryotes, and Archaea. In this study, it was shown that S1 domains of bacterial, eukaryotic, and archaeal proteins have a low percentage of identity, which indicates the uniqueness of the scaffold and is associated with protein functions. Assessment of the predisposition of tertiary flexibility of S1 domains using computational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 58 publications
1
21
0
1
Order By: Relevance
“…The S1 domain can be found in different eukaryotic protein families and protein complexes in different number variations [ 6 ]. An assessment of the susceptibility of the flexibility of S1 domains showed similar structural features and revealed functional flexible regions that are potentially involved in the interaction of natural binding partners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The S1 domain can be found in different eukaryotic protein families and protein complexes in different number variations [ 6 ]. An assessment of the susceptibility of the flexibility of S1 domains showed similar structural features and revealed functional flexible regions that are potentially involved in the interaction of natural binding partners.…”
Section: Introductionmentioning
confidence: 99%
“…These facts allowed us to assume that the flexibility ratio in a separate domain is related to its role in S1 activity and functionality: a more stable and compact central part in multi-domain proteins is a vital for RNA interaction; terminal domains perform other functions [ 7 , 8 ]. Moreover, the obtained results correlate with the presence of S1 domain repeats in the S1 domain-containing proteins in the range from one (bacterial and archaeal) to fifteen (eukaryotic), and that is apparently due to the necessity of individual proteins to increase the affinity and specificity of binding to ligands [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the S1 domain adopt a five-stranded antiparallel β barrel in which residues Phe-19, Phe-22, His-34, Asp-64, and Arg-68 are believed to infer its RNA-binding ability [ 46 ]. S1 domain repeats ( Figure 1 ) vary from one to 15 in different species [ 47 ] and have been identified in RNase E endonuclease (RNase E), RNase II exonuclease (RNase II), transcription factor NusA, and C. elegans EMB-5 [ 46 ], which play a crucial role in mRNA turnover, rRNA processing, and translational initiation [ 48 , 49 , 50 , 51 ]. In addition, S1 domain repeats are also found in other RNA-associated proteins, such as bacterial polynucleotide phosphorylase (PNPase) [ 52 , 53 ], bacterial translation initiation factor 1 (IF1), eukaryotic eIF2a [ 54 ], and the RNA helicase-like protein PRP22 found in yeasts [ 55 ].…”
Section: Domain or Motif Features Of Crm Ppr Dbrh And Sdp Protementioning
confidence: 99%
“…In addition, S1 domain repeats are also found in other RNA-associated proteins, such as bacterial polynucleotide phosphorylase (PNPase) [ 52 , 53 ], bacterial translation initiation factor 1 (IF1), eukaryotic eIF2a [ 54 ], and the RNA helicase-like protein PRP22 found in yeasts [ 55 ]. Furthermore, a recent study has demonstrated that the amino acid sequence homologies of S1 domains are approximately 43% in archaea, 51% in bacteria, and 46% in eukaryotes, and that the residues of Phe-28, Asp-66, and Arg-71 in archaea and Phe-25, Asp-68, and Arg-71 in eukaryotes are highly conserved [ 47 ]. These findings suggest that S1 domains are diverse with a low sequence identity among different species.…”
Section: Domain or Motif Features Of Crm Ppr Dbrh And Sdp Protementioning
confidence: 99%
“…в S1 домене, по-видимому, может быть вовлечена во взаимодействие с природными лигандами. Таким образом, полученные результаты показывают, что число возможных функций для эукариотических белков, содержащих S1 домены, увеличивается за счёт увеличения количества структурных доменов и гибких перемычек между доменами, а не из-за изменения характеристик отдельных структурных доменов [4].…”
unclassified